The Effect of Perioperative Forced Air Warming Blanket on Older Adult Patients Undergoing Spinal Surgery with General Anesthesia - Faisal Toheed, Abdul Bary, Neelam Noreen, Mobasher Ahmad Saeed, Muhammad Iqbal, Sajjad Rasool Chaudhary, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Elderly patients undergoing spinal surgery under general anesthesia are particularly susceptible to perioperative hypothermia due to impaired thermoregulation and prolonged surgical durations. Hypothermia is associated with multiple adverse outcomes, including increased blood loss, postoperative shivering, delayed wound healing, and prolonged hospitalization. Forced air warming (FAW) blankets offer a potential solution by actively maintaining normothermia during surgery. Objective: To evaluate the effectiveness of perioperative forced air warming blankets in maintaining intraoperative core temperature and improving postoperative outcomes in older adult patients undergoing spinal surgery under general anesthesia. Methods: This prospective observational study was conducted at Prince Sultan Cardiac Center, Riyadh, Saudi Arabia, and Bolan Medical Complex Hospital, Quetta, Pakistan, from June 2022 to May 2023. A total of 80 patients aged 60 years and above scheduled for elective spinal surgery were enrolled and divided into two groups (n=40 each). Group A received perioperative FAW, while Group B received standard passive insulation. Core temperatures were recorded preoperatively, intraoperatively, and postoperatively. Postoperative outcomes assessed included shivering, estimated blood loss, wound complications, and hospital stay duration. Statistical analysis was performed using SPSS version 26.0, with significance set at p<0.05. Results: Intraoperative core temperature was significantly higher in Group A compared to Group B throughout the surgery (p<0.001). Postoperative shivering was markedly lower in the FAW group (5% vs. 27.5%, p=0.006). Group A also exhibited significantly reduced blood loss (310 ± 55 mL vs. 385 ± 63 mL, p=0.01) and shorter hospital stays (3.8 ± 1.1 days vs. 4.7 ± 1.3 days, p=0.02). Wound complications were less frequent in the FAW group but did not reach statistical significance. Conclusion: Perioperative forced air warming blankets effectively maintain normothermia and improve postoperative recovery in elderly patients undergoing spinal surgery under general anesthesia. Routine incorporation of FAW into perioperative care protocols is strongly recommended for elderly surgical populations. Keywords: Forced air warming, perioperative hypothermia, spinal surgery, elderly patients, general anesthesia, postoperative recovery, thermoregulation.